PENGARUH FDI, KUALITAS TENAGA KERJA, DAN TRADE OPENNESS TERHADAP MANUFACTURING VALUE ADDED DI BEBERAPA NEGARA ASEAN - Ramadhana; Anak Agung Bagus Putu Widanta; Ni Luh Karmini; I Wayan Sukadana (Berajah Journal, 2026)
Manufacturing Value Added (MVA) is an important indicator used to measure the contribution of the manufacturing sector to a country’s economy. Countries in the ASEAN region exhibit diverse developments in the manufacturing sector, which are influenced by various economic factors such as FDI, labor quality, and trade openness. This study aims to analyze the effect of FDI, labor quality, and trade openness on Manufacturing Value Added in several ASEAN countries during the 2015–2023 observation period. The method used in this study is panel data regression analysis with a significance level of five percent, employing the Fixed Effect Model (FEM) approach. The results show that simultaneously, FDI, labor quality, and trade openness have an effect on Manufacturing Value Added. Partially, FDI has a positive but insignificant effect on MVA, while labor quality and trade openness have a positive and significant effect on MVA. These findings indicate that improvements in labor quality and trade openness play a stronger role in driving the growth of the manufacturing sector compared to direct foreign investment inflows. Therefore, policies focusing on human resource development and increasing trade integration are needed to strengthen the sustainable contribution of the manufacturing sector